2016
DOI: 10.1111/nph.14257
|View full text |Cite
|
Sign up to set email alerts
|

High‐level expression of a novel chromoplast phosphate transporter ClPHT4;2 is required for flesh color development in watermelon

Abstract: Chromoplast development plays a crucial role in controlling carotenoid content in watermelon flesh. Modern cultivated watermelons with colorful flesh are believed to originate from pale-colored and no-sweet progenitors. But the molecular basis of flesh color formation and regulation is poorly understood. More chromoplasts and released carotenoid globules were observed in the red-fleshed fruit of the 97103 cultivar than in the pale-colored fruits of the PI296341-FR line. Transcriptome profiles of these two mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 58 publications
0
54
0
Order By: Relevance
“…This finding suggested that both ABA metabolism and signal transduction pathways may be involved in the ripening and quality trait evolution. The importance of ABA signaling pathways is highlighted by the fact that exogenous ABA treatment could not turn on or accelerate the ripening process of either the wild PI296431-FR or the semi-wild accession PI179878 [51]. In addition to phytohormone accumulation and signaling, there is evidence that ripening is also regulated by both DNA methylation and the action of specific transcription factors [2].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that both ABA metabolism and signal transduction pathways may be involved in the ripening and quality trait evolution. The importance of ABA signaling pathways is highlighted by the fact that exogenous ABA treatment could not turn on or accelerate the ripening process of either the wild PI296431-FR or the semi-wild accession PI179878 [51]. In addition to phytohormone accumulation and signaling, there is evidence that ripening is also regulated by both DNA methylation and the action of specific transcription factors [2].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the ClPHT4;2 expression levels were closely correlated with flesh carotenoid contents among 198 watermelon accessions. Furthermore, down-regulation of ClPHT4;2 expression in transgenic watermelons decreased the fruit carotenoid accumulation (Zhang et al, 2017). Above all, plant PHT4s play various roles, further investigating their functions, especially in crops, will facilitate the development of crops with desired agronomic traits.…”
Section: Phylogenetic Analysis and Roles Of Plant Pi Transportersmentioning
confidence: 99%
“…In maize, though MYCS was found in the promoter of some AM-inducible ZmPHT1s , some ZmPHT1s without the MYCS element, such as ZmPHT1;2 , ZmPHT1;4 , ZmPHT1;7 , and ZmPHT1;9 , also upregulated by AM, implying that new regulation element(s) might exist in the promoter regions of these genes (Liu F. et al, 2016). Most recently, Zhang et al (2017) identified two TFs (ClbZIP1 and ClbZIP2) from watermelon, binding to the promoter of ClPHT4;2 , which shed light on our understanding of the regulatory mechanisms of PHT4s expression.…”
Section: Regulation Of Pi Transportersmentioning
confidence: 99%
“…TAI activity in the vacuole may lead to accumulation of symplastic glucose in the cell, which may stimulate chromoplast formation, as shown for watermelon (Zhang et al, 2017).…”
Section: Resultsmentioning
confidence: 86%
“…There is some evidence that sugars can act as signaling molecules to activate carotenoid biosynthesis and, as a result, the fruit acquires a different color. For example, changing the sugar concentration in mandarin (Citrus unshiu), watermelon (Citrullus lanatus) and tomato fruits alters their pigmentation (Iglesias et al, 2001;Telef et al, 2006;Zhang et al, 2017). Thus, a connection can be proposed between the sucrose-hexose ratio and the synthesis of carotenoids.…”
mentioning
confidence: 99%